2008
DOI: 10.1002/mds.21802
|View full text |Cite
|
Sign up to set email alerts
|

Improved gait parameters after robotic‐assisted locomotor treadmill therapy in a 6‐year‐old child with cerebral palsy

Abstract: Task-specific body-weight-supported treadmill therapy improves walking performance in children with central gait impairment. Modulation of spinal networks and improvement of muscle energy consumption are thought to contribute to this effect. Robotic-assisted treadmill therapy enabled by a driven gait orthosis (DGO) has been established for adults and shown to provide significant improvements in individuals with spinal cord injury and stroke. Recently a pediatric DGO has been developed. Here, we report the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…Previous studies suggested promising effects in walking ability, endurance and lower extremity function in patients with different neurological disorders such as stroke [4][5][6][7], spinal cord injuries (SCI) [8][9][10][11], traumatic brain injuries (TBI) [12], multiple sclerosis (MS) [13], and cerebral palsy (CP) in childhood and adolescence [14,15]. A recent review on electromechanical-assisted gait training for walking after stroke has shown significant increases in walking ability and walking capacity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested promising effects in walking ability, endurance and lower extremity function in patients with different neurological disorders such as stroke [4][5][6][7], spinal cord injuries (SCI) [8][9][10][11], traumatic brain injuries (TBI) [12], multiple sclerosis (MS) [13], and cerebral palsy (CP) in childhood and adolescence [14,15]. A recent review on electromechanical-assisted gait training for walking after stroke has shown significant increases in walking ability and walking capacity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Robot-assisted gait training with the driven gait orthosis Lokomat was shown to be an effective way of restoring walking ability in patients with neurological gait disorders due to stroke [6], [7], incomplete spinal cord injury [8]- [11], multiple sclerosis [12], and in children with cerebral palsy [13], [14]. The main advantage of mechanized gait training in comparison to manually assisted gait training or conventional physical therapy is that the therapist is relieved from the high physical strain when guiding the legs and stabilizing the body of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the spatial precision of the movement, the mechanical impedance of the linear drives is high. The feasibility and effectiveness of training programs with the DGO Lokomat were shown in subjects having suffered stroke [6], [7], incomplete spinal cord injury [8]- [11], multiple sclerosis [12], and in children with cerebral palsy [13], [14]. A clear advantage of training with the DGO Lokomat-as well as with other gait training devices-is that the therapist is relieved from the physical strain of manually guiding the patients' legs or stabilizing the patient's torso [6].…”
mentioning
confidence: 99%
“…One way to combine rehabilitation and engage the child in the activity is through games, where the child must perform rehabilitative actions (such as stretching, grasping etc) in order to win. It has been proven that game or virtual reality activities not only help engage the children but also actually improve their motor skills [4,5]. Moreover, some studies suggest that children with CP might have a risk of getting worse due to musculoskeletal growth [19,9], emphasizing the need for rehabilitation for children.…”
Section: Cerebral Palsymentioning
confidence: 99%